Strategy of Sumberejo Woman Farmers Groupin Implementing Life Skills Education throught the Srikandi Factory Entrepreneurship ProgramTowards a Smart Village - Anwar, Mila Maulidya; Purwito, Lasi; Listyaningrum, Anggia (Universitas Negeri Malang, 2024)
Life or life skills can be interpreted as a person's ability to survive which includes the ability to think, theability to communicate, the ability to build cooperation, and have a good character in acting, responsible, ethical incommunity life. The purpose of this study (1) to describe the strategy of the peasant women Group in implementinglife skills education into the Srikandi Factory Entrepreneurship Program (2) to describe the process of the peasantwomen Group in pursuing the Srikandi Factory Entrepreneurship Program towards Smart Village (3) to determine thefactors that support and inhibit the Sumberejo village KWT in implementing skills education Living Towards A SmartVillage. This study uses qualitative research methods with the type of case study approach. The location of the studywas conducted in the peasant women's group of Sumberejo Village, Batu City. Data collection techniques used byresearchers are interviews, observation, and documentation studies. Data analysis techniques in this study are datareduction, data presentation, and drawing conclusions from the data obtained. Checking the validity of the data is donethrough engineering triangulation and source triangulation. The results showed that the strategy carried out by thepeasant women group is implemented with life skills education through the Srikandi Factory program. Some of thestrategies carried out by KWT Sumberejo include holding regular meetings within a week, implementing the trainingsthat have been followed to supplement the program at Srikandi Factory, creating Karya Wisata activities, and recruitingbusiness partners. Some of these activities proceed through the entrepreneurship-based Srikandi Factory programwhose implementation process uses 3 aspects of smart villages, including aspects based on smart communities, smartenvironments, and smart economies. This process is KWT Sumberejo's strategy to implement life skills educationtowards a smart village. Keywords: Life Skills Education Strategy, Farmer Women Group, Smart Village